Under sentence of death : lynching in the South - Brundage, W. Fitzhugh (William Fitzhugh), 1959- (History of capital punishment., 1997)
This collection of essays explores "such topics as same-race lynchings, black resistance to white violence, and the political motivations for lynching ... The book raises important questions about Southern history, race relations, and the nature of American violence."--Page 4 of cover.